The impact of knowledge creation on employee engagement from the perspectives of exploitation and exploration - Irene, Wei Kiong Ting; Sui, Hai Juan; Mohd Ridzuan, Darun; Liu, Yao; Qian, Long Kweh (Inderscience Enterprises Ltd., 2020)
The main purpose of this study is to assess the impacts of knowledge creation on employee engagement from both exploration and exploitation perspectives. After identifying that knowledge creation could facilitate employee engagement from a literature review, the study proposed a model of knowledge creation toward employee engagement. A survey questionnaire was developed accordingly. With a stratified sampling method, data were collected from the academic staff of one public and one private university located in Malaysia. A total of 200 academic staff members participated in this study. Linear regression analysis was performed to test how knowledge creation (i.e., exploration and exploitation) affects employee engagement. Statistical results show that the exploration and exploitation of knowledge creation positively and significantly affect employee engagement. The proposed model could aid universities in utilising knowledge creation practices to engage employees so as to attain and sustain competitive advantage.